Comparison of a Tumor-Ratio–Metastasis Staging System and the 8th AJCC TNM Staging System for Gastric Cancer - Zhang, Miaoquan; Ding, Chao; Xu, Lin; Ou, Biyi; Feng, Shoucheng; Wang, Guoqiang; Wang, Wei; Liang, Yao; Chen, Yingbo; Zhou, Zhiwei; Qiu, Haibo (Frontiers in Oncology, 2021)
Background Despite the implementation of the 8th American Joint Committee on Cancer (AJCC) TNM staging system for gastric cancer (GC) in 2017, it still holds a significant level of stage migration which affects patients’ proper classification and accurate prognosis. Here, to reduce this effect, we evaluated the prognostic value of a lymph node ratio (LNR) and established a novel tumor–ratio–metastasis (TRM) staging system. Method The data of 15,206 GC patients from the Sun Yat-sen University Cancer Center (Training set; n=2,032) and the US Surveillance, Epidemiology, and End Results (SEER) database (Validation set; n=13,174) were analyzed. The training set was classified into 5 LNR categories, based on which the novel TRM staging system was constructed. The overall survival (OS) between the TRM and AJCC TNM systems was compared in the training set and validated in the validation set. The likelihood ratio x2, liner trend x2, C-index, and Akaike information criterion (AIC) values were used to measure the discriminatory ability between the two different staging systems. Decision curve analyses (DCAs) were conducted to test the clinical value of the two staging systems. Result The patients were classified into the following categories: LNR0: 0%, LNR1: 0%<LNR ≤ 10%, LNR2: 10%<LNR ≤ 25%, LNR 3a: 25%<LNR ≤ 60%, and LNR 3b: LNR>60%. Univariate analyses demonstrated that the log-rank x2 of the LNR stage (Training/Validation set: x2 = 463.1/2880.8) was larger than the AJCC pN stage (Training/Validation set: x2 = 281.5/2240.8). For both the training set and validation set, stratified analyses using the Kaplan-Meier method identified significantly heterogeneous OS in every pN category but only one using the LNR. The TRM staging system had higher likelihood ratio x2, liner trend x2, C-index and smaller AIC values than the TNM system. Conclusion The TRM staging system demonstrated improved homogeneity and discriminatory ability in predicting the prognosis of GC patients compared with the AJCC TNM staging system.